"Planting these plants is special because they have been shared with us by the White House": American Grown's kitchen garden as a gastrogovernmental space. Issue 3 (3rd July 2017) - Kjær, Katrine Meldgaard
ABSTRACT: This article presents a critical reading of American Grown, a cookbook/how-to gardening book published by Michelle Obama in 2012. The article argues that while American Grown may at first glance seem like a coffee table-style book about the 2010 planting of the White House kitchen garden, it should in fact be read as a piece of public health communication and a gastrogovernmental text born out of social panic over the contemporary obesity epidemic. Using insights from cultural food studies and critical obesity studies, the article presents the concept of gastrogovernmentality as an analytical tool to argue that the kitchen garden in American Grown acts as a public-personal space of social regulation, where certain types of social identities and behaviors are promoted as the "solution" to the obesity epidemic.